Development of bio-based 2T engine oil in marine engine application / Babooraman Shanmuganathan - Babooraman, Shanmuganathan (2020)
Two-storke enginers are simple and lightweight two-cycle spark ignition engine with no oil sump is needed. The use of bio-based lubricants was analyzed to replace commercial mineral and synthetic-based lubricants. Lubricants were prepared by mixing three components of oil which comprise of base oil, additives, and solvent. In this research, four samples of base oil had been prepared with a different weight ratio of the PFAD-NPGester and Type II mineral. Then each of the simples were added with a similiar weight ratio of additives and solvent. A commercial lubricant was used as areference lubricant to be compared with samples prepared. A viscometer was used to determine the viscosity index and density of each sample and reference lubricant. Next, afour-ball tribo-tester was used to evaluate friction and wear prevention characteristics ineach sample and rreference lubricant. Finally, an idle operation mode had been conductedon a two-stroke brush cutter engine to determine the effect of reference lubricant and bio-based lubricant towards carbon deposition on the spark plug. Lubricant sample B coptrises a 40% weight percentage of PFAD-NPG ester and a 60% weight percentageof Type II mineral oil. Sample B had exhibited the highest viscosity index of 154.4 compared to other samples and reference lubricants with the lowest viscosity index of 129.5. This enables it to form a thick lubricantion film between moving surfaces. Based onfriction evaluation results, it can be seen that Sample B has recorded the lowest COF value compared to reference lubricant. Throught the WSD analysis conducted, sample B was record to have the lowest WSD value is 580.69mm compared to the reference lubricant which is 794.35mm. Sampel B caused the least wear on the threelower ball bearings used in the tribo-tester experiment. For the engine performance test, sample B has undergone complete combustion with fuel without leaving any carbon deposits on electrodes and insulator tips. In conclusion, the bio based lubricant has improved engine efficiency and reduce wear in a two-stroke engine.